Development of MSME Marketing Strategy for Wonogiri Mas Ram Meatballs - Lia Awalia; Firna Is Tsaniyah; Dwi Epty Hidayaty; Santi Pertiwi Hari Sandi (PT FORMOSA CENDEKIA GLOBAL, 2023)
The method used is descriptive method as evidenced by the results of observations. The results showed that external and internal factors in the marketing efforts of the Wonogiri Mas Ram Meatballs, namely, strengths: full tendon meatballs with abundant beef tendons, strategic business location, clean eating places, consistency of the same taste since 28 years and good service. Good. Weaknesses: limited business capital, simple management, lack of marketing personnel. Opportunities: interest in meatballs is increasing, consumer interest in meatballs is very high, advances in technology and information, people's needs are very high, and have regular customers. Threats: rising fuel prices, rising raw materials, increasing number of meatball competitors, and customer sensitivity to price.